Mental Health and Social Connectedness During the COVID-19 Pandemic: An Analysis of Sports and E-Sports Players - Soares, Ana Karla Silva; Goedert, Maria Celina Ferreira; Vargas, Adriano Ferreira (Frontiers in Psychology, 2022)
Social connection is essential to good mental health. The epidemiological and public health literature shows that social connection protects and promotes mental health, being an important clinical tool for reducing anxiety, depression, and stress. Thinking in the broad sense of connection, that is, feeling and perceiving oneself connected with the environment, applied to the context of sport, it is suggested that social connection could be related to the interactions in the practice of sport. Recently, the pandemic context in which the world finds itself has inspired studies that sought to relate aspects of social connection with mental health variables (e.g., well-being, loneliness, and stress). Although playing sports can promote mental health, there are few findings on the topic in the context of a pandemic and with physical sports and electronic sports (e-sports) players. In this sense, the present study aims to assess the extent to which social connection and mental health indicators are correlated in a sample of sports and e-sports players. The participants were 401 Brazilian physical sports (N = 199, 49.6%) and e-sports players (N = 202, 50.4%), mostly male (53.1%) and single (59.9%), who filled in the Social Connectedness Scale (SCS), the Depression, Anxiety and Stress Scale (DASS), and demographic questions. The results indicated that social connection was negatively correlated with anxiety (r =.- 37), depression (r =.- 54), and stress (r =.- 39). Social connection was also a predictor of anxiety (β =.- 37), depression (β =.- 54), and stress (β =.- 39). When comparing sports and e-sports players, a statistically significant difference was identified in the levels of social connection [t (398) = -3.41; sportsmean (SD) = 4.53 (1.14); e-sportsmean (SD) = 4.14 (1.15)] and depression [t (396) = 2.90; sportsmean (SD) = 1.10 (.89); e-sportsmean (SD) = .85 (.81)]. These findings suggest that better social connection can effectively reduce indicators of anxiety, depression, and stress in sports and e-sports players, favouring their mental health.